Hydropower and Dams (H and D) : Strengthening Climate-Informed Project Design - World Bank Water Global Practice; Global Water Security and Sanitation Partnership (Washington, DC, 2022)
The growing impact of climate change on the design and operations of dams and the inherent complexity of dam projects (often multi-purpose) require the capacity to adopt increasingly strict global standards and to mainstream resilience and low-carbon considerations in water infrastructure in which dams are a critical component. Dams and reservoirs are both helpful for applying water resources management principles to build resilience to climate change and vulnerable to risks related to climate change.